Diversity and Inclusion in an Orthopaedic Surgical Society: A Longitudinal Study. Issue 7 (August 2021) - Singleton, Ian M.; Poon, Selina C.; Bisht, Roy U.; Vij, Neeraj; Lucio, Francisco; Belthur, Mohan V.
Abstract : Background: Diversity and inclusion are critical to providing the best possible health care. Previous studies have shown that diversity among physicians increases cultural competency, which in turn enhances the quality of care provided and increases minoritized patients' participation in decisions regarding their health care. However, physician diversity in both race and sex is lacking in orthopaedic surgery. This study seeks to determine the sex and racial diversity in the membership and leadership of the Pediatric Orthopaedic Society of North America (POSNA). Methods: POSNA membership and leadership were reviewed for the years 2010, 2015, and 2020. This data was gathered from membership directories and committee reference books. All North American Active Members' race/ethnicity and sex were recorded for each year. The categories for race/ethnicity are Caucasian, East/South/Middle Eastern Asian American (Asian), Hispanic/Latin/South American (HLSA), and African American. Results: From 2010 to 2020, Active Members of POSNA increased from 608 to 818, and the percentage of female (14.6% to 23.7%), Asian (7.4% to 11.2%), HLSA (2.5% to 2.9%), and African American membership (1.6% to 1.8%) increased. Male (85.4% to 76.3%) and Caucasian (88.5% to 84.0%) membership decreased. From 2010 to 2020, male leadership decreased on both the Board of Directors and Committee Chairs (89.5% to 81.8% and 86.4% to 64.7%, respectively), as did Caucasians (94.7% to 81.8% and 90.9% to 88.2%, respectively). The number of Asian members holding positions on both the Board of Directors and Committee Chairs increased (0% to 18.2% and 4.5% to 11.8%, respectively) as did the number of females (10.5% to 18.2% and 13.6% to 35.3%, respectively). HLSA and African American members were proportionally represented in leadership for the years 2010 and 2015. Conclusions: Membership in POSNA has increased between 2010 to 2020 for every diversity category examined and POSNA membership exhibits significantly more diversity than the orthopaedic specialty as a whole. Leadership as a whole is more diverse in 2020 than it was in 2010. Level of Evidence: Level II—retrospective.